PENGARUH LATIHAN ONE-LEG-BODY-WEIGHT-CALF-RAISE ON A STEP TERHADAP KEKUATAN OTOT TUNGKAI SMP 25 PEKANBARU YANG MENGIKUTI EKSTRAKULIKULER BOLA VOLI - Putri, Nidya; Wijayanti, Ni Putu Nita; ', Slamet (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The case in the research , kind of this research is experimental research kind. That the strength of leg muscle of smp 25 volleyball team pekanbaru is still adverse. It seen from training that done in the game, when player does a smash.the jump is still adverse. The purpose of this research is to see the effect of one leg body weight calf raise on a step training toward the strength of leg muscle smp 25 pekanbaru. This research kind is ps eudo research to see the effect from training form. population in this research is 12 players of smp 25 volleyball team. Sampling technique is purposivesampling, it means the sampling technique with particular consideration. The instrument in this research is leg dynamometer to see the strength of leg muscle. Analysis was done using t-test. Based on data discussion analysis.that can be concluded there is effect of one leg body weigth calf raise on a step training againts leg muscle of smp 25 pekanbaru volleyball team as evidance by t count 1.834>t table 1.796 pada α=0,05.Keyword : one leg body weight calf raise on astep, Strength